The Role of Accounting Information System in Planning and Control of Sales at PT. Pupuk Kaltim (Surabaya Branch) - Ramadhan Wiprayoga (Jurnal Ilmiah Mahasiswa FEB, 2015)
Sales are one of the significant activities for company survival heavily upon the success of this activity, if sales increase so that companies had progress and vice versa. Successful of advisability management in doing his duty are dependent upon ability decision by using relevant and properly information.Accounting information system sales in part of information systems specialized for processing data coming from sales transactions only so that accounting information is generated that related to sales only. From the above condition, sales requires a sales accounting information system transactions that understands both carry out transactions, record book keeping and also reporting transactions.The purpose of this research is to find out how the role of accounting information system in decision making so that sales can do the planning and controlling of sales at PT. Pupuk Kaltim Surabaya Branch. The results showed that PT. Pupuk Kaltim Surabaya Branch has two sales systems which are subsidized fertilizer and non-subsidized fertilizer. In sales subsidized fertilizer is the main case must be considered to controlled the fertilizer available on the market according to farmer’s needs, in case if the fertilizer is too much in market it will cause possibility fertilizer to be leaked to another. Sales non-subsidized fertilizer different with subsidized fertilizer, sales for non-subsidized fertilizer can be served from the market request how much they want. Sales prices used the international market price. The main thing in decision making for the sales of non-subsidized fertilizer is determination of the sales price. Determination should consider several aspects that took place in the international market and domestic market. The role of accounting information in planning and control in sales at PT. Pupuk Kaltim Surabaya Branch for gathering information is complete and relevant, so it could take a decision for the right sale.Keywords: Sales, Accounting Information Systems, Sales Transactions.